A Study of Correlation Between Hand Dimensions In Indian Population (Indian Internet Journal of Forensic Medicine and Toxicology, 2011)
Various dimensions of the hand have been used for the determination of sex, and stature of an individual in forensic investigations. However, the data on correlation between the different hand dimensions is very limited. The present research aims at analysing the correlation between the dimensions of hand. The study was conducted on 500 Indian medical students (230 males and 270 females) at Kasturba Medical College, Manipal. A significant correlation is observed between the different dimensions of hand. Besides, medico-legal implications the study will also prove to be of significance in plastic and reconstructive surgery of hand.
Keywords: Forensic anthropology; Identification; Correlation; Hand dimensions